OPTIMALISASI PENGETAHUAN REMAJA TENTANG KESEHATAN REPRODUKSI REMAJA DI PANTI ASUHAN KECAMATAN NGAWI - erwin kurniasih; Rini Komalawati (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2022)
Adolescence is a period of transition from the stage of child development to adulthood where adolescents need to adapt in order to accept these changes. In fact, data from the 2017 SDKI shows that adolescent knowledge about reproductive health is still minimal because Indonesian people still regard sexuality as something that is taboo and not to be discussed openly. The results of the assessment at the Ngawi District Orphanage found that reproductive health education materials specifically had never been given by orphanage supervisors or school teachers so that the Akper Pemkab Ngawi community service team carried out activities to optimize adolescent knowledge about reproductive health. This activity was carried out for 3 days with the method of providing counseling and forming groups (peer groups) for the discussion process. The evaluation was carried out using the post test method and observation of the peer group discussion process. The results of the evaluation showed an increase in adolescent knowledge on post test scores.